Optimasi Konsentrasi Glukosa dan Waktu Inkubasi Terhadap Bobot β-Glukan Jamur Schizophyllum commune - Tri Rahayu Apriyani; Nuraeni Ekowati; Nuniek Ina Ratnaningtyas (Fakultas Biologi Universitas Jenderal Soedirman, 2022)
The main purpose of this study was to determine the effect of the interaction between glucose concentration and incubation time on the growth of fungi S. commune and also the weight of β-glucan was used to determine the best glucose concentration and incubation time for the growth of fungi S. commune and β-glucan production. The research was conducted by experimental method of completely randomized factorial design (CRD factorial) with two factors carried out in three repetitions. The treatments provided included variations in glucose concentration (G) with three levels, namely 10 g/L (G1), 20 g/L (G2), and 30 g/L (G3), and variations in incubation time (W) with three levels, namely incubation time of 20 days (I1). , incubation time of 25 days (I2), and incubation time of 30 days (I3). Variables which used in this research independent and dependent variables. The independent variables were glucose concentration and incubation time, while the dependent variables were fungal mycelium growth and β-glucan production. The main parameter observed was β-glucan weight. The supporting parameters were dry biomass weight and the final pH medium. Data analysis was performed by Analysis of Variance (ANOVA) at 95% accuracy levels, followed by Duncan's test (Ducan Multiple Range Test). The results showed that glucose concentration and incubation time were significantly affected to the growth and production of β-glucan fungus S. commune. Glucose concentration of 30 g/L and incubation time of 25 days was the optimum glucose concentration and incubation time for the growth of S. commune fungus, and also glucose concentration of 30 g/L and incubation time of 25 days was the optimum glucose concentration and incubation time for β-glucan production of S. commune.